Effect of feeding total mixed ration blocks on productive performance of crossbred dairy cattle - Sahib, Lasna; S, Pramod; B, Bibin Becha; R, Thirupathy Venkatachalapathy (Indian Journal of Dairy Science, 2020)
A feeding trial of four weeks was conducted using forty crossbred dairy cattle reared under intensive system. The animals were divided into 2 groups, based on milk yield, parity and stage of lactation and fed either a commercially available total mixed ration (TMR) blocks or conventionally available compounded cattle feed (in form of pellet) and green grass separately at different times of the day. The results indicated that the total daily milk yield was significantly lower (p<0.01) in the group fed TMR blocks when compared to the group fed conventionally. Feeding TMR blocks or conventional feeding with compounded cattle feed did not have any significant effect on the milk composition viz fat, solids not fat (SNF), lactose and protein content. The results suggested that feeding TMR blocks showed negative impact on milk production when compared to conventional feeding system with compounded cattle feed. Â